Coproduced resources to support parents caring for children with gastrostomies. Issue 2 (25th August 2022) - Page, Bethan; Harrop, Emily; Beale, Tania; Boyce, Katherine; Smith, Colette; Butler, Siobhan; Sharrard, Alison; Vincent, Charles; Lee, Alex CH
Abstract : Objective: To describe and disseminate a package of support for parents who care for children with gastrostomies, consisting of a library of videos and resources to support families from referral for gastrostomy surgery, to long-term support at home. Methods: The resources were systematically developed and evaluated by parents, hospital and community-based nurses, paediatricians, a surgeon and researchers. Results: The videos empower families, reduce their anxiety and increase their confidence, providing support throughout the families' journey. Surveys and feedback from parents and clinicians show that the video library is seen as providing clear and comprehensive guidance and is suitable for integration into routine practice. To effectively disseminate these resources across a region, the videos need to be shared widely with relevant community and hospital-based teams, and shared through parent networks. The videos should be viewed as one part of a wider package of training and support, in combination with hands-on-practice and clinical support. Conclusions: The resources described have been developed with and for families. Critically the videos are founded in the lived-experience of families, as well as the expertise of clinicians from community and hospital services. Similar resources are needed to support families performing other types of specialist care. The resources are freely available to any parent or clinical team.